Using assessments to improve process safety culture. Issue 2 (13th September 2013) - Ogle, Russell A.; Morrison, Delmar "Trey"; Dee, Sean J.
<x xml:space="preserve">Abstract</x> Deficiencies in conduct of operations and operational discipline can lead to a decline in the quality of an organization's process safety culture and an increase in the likelihood of process safety incidents. A process safety assessment is one tool especially suited for identifying and correcting organizational safety culture deficiencies. Both AIChE/CCPS and API offer recent guidance documents on how to conduct effective assessments of process safety management systems. This article first introduces some basic concepts from game theory and applies them to the methodology of process safety assessments. A conceptual framework for the implementation of the process safety assessment process with balanced positive and corrective actions will be described. Assessment guidelines typically focus on the negative outcomes—correcting deficiencies. This article argues that the assessment process must also use the positive outcomes—the compliance successes—to provide positive reinforcement to the process safety culture. Implementing this strategy is consistent with pragmatic management practices and is supported by empirical studies in behavioral science. Finally, this article discusses how these ideas fit within the framework of AIChE/CCPS and API guidance documents. © 2013 American Institute of Chemical Engineers Process Saf Prog 33: 148–151, 2014